Restorasi Filsafat, Dialog Mutual, dan Syari'ah: Ibn Rusyd dan Reformasi Islam dalam Fashl al-maqal - Ibnu Rusyd (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Paramadina, 2023)
Ibn Rushd is one of the most important philosophers in the classical world of Islam. Without him, Aristotle would have remained a great mystery to the Western scientific world. It was he, who managed to provide the longest commentary on almost all of Aristotle's works, and his commentary, along with some of the doctrines of Averroism, created the great rationalist movement in the Latin West. However, unlike his philosophical dimension, which some Muslim scholars find too Aristotelian and therefore more impactful in the West and not in the Islamic world, Ibn Rushd's Islamic reform dimension has not received enough attention. I expose Ibn Rusyd's reform, in this study, as contained in one of his books, Fasl al-maqal fi taqrir ma bayna ash-shari'ah wa al-hikmah min al-ittisal (The decisive book on the certainty that there is a connection between shari'ah and philosophy). There are at least three main themes in his reform: restoration of philosophy, restoration of mutual dialogue, and restoration of the shari'ah. With these three themes of reform, we will realize not only Ibn Rushd's contribution to philosophy, but also his great concern for a number of crises in Islam, and for solutions to resolve them.